Structural Holes and Online Bridging: A qualitative study of the Social Structures surrounding Academic Entrepreneurs and Technology Entrepreneurs in the East Midlands region of the United Kingdom - Ling, Simon (2009)
This management project is divided into two parts that explore the social structures surrounding academic entrepreneurs and technology entrepreneurs in the East Midlands region of the United Kingdom. The first part researches the nature of the social structures surrounding the two entrepreneurial groups and the second part produces a business plan to exploit opportunities present within these social structures. Part A: Structural Holes Research The aim of the research was to use social capital theory as a framework to analyse the social structures surrounding academic entrepreneurs and technology entrepreneurs during early stage commercial activity, in order to provide an overall view of the nature of the social structures and identify the issues present within each inhibiting economic development. To achieve this information from the available published literature was compared to the findings from a series of interviews held with entrepreneurs and other members of the social structure. The outcome of the research was the production of two models of the social structures surrounding each type of entrepreneur as well as the identification of a number of issues that effect early stage commercial activity within the East Midlands region. The three most significant issues resulted as a pre-seed funding gap that inhibits the level of technology entrepreneurship, a research commercialisation gap that reduces the level of academic entrepreneurial activity, and an early stage management support availability gap that hinders access to early stage expertise, knowledge, and advice. Part B: Online Bridging Business Plan The aim of the business plan was to use the research in part A to develop a proposal for a specialist online network that utilises a combination of tools to overcome issues within the social structures to increase member interaction across the network. The business plan provided is a complete and rigorous document that includes a description of the business and the proposed service offering, an analysis of the market environment, detail of the business strategy and objectives, a proposition for investment, identification of key risks, and a complete set of financials for five years.